2023
DOI: 10.1007/s11104-023-06166-5
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm and soil microbial communities in flower strip mixtures

Abstract: Aims Incorporation of flower strips is an agricultural measure to increase aboveground biodiversity and ecosystem services. Although soil communities are key components of terrestrial biodiversity and drive important ecosystem services, their abundance, diversity, and composition in flower strips remain largely unexplored. Here, we shed light on earthworms and soil microorganisms in flower strips. Methods We sowed a grassy field margin vegetation as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
1
1
0
Order By: Relevance
“…In their meta-analysis, Zhang et al [53] identified an average 10% increase in soil fauna diversity in more diverse plant mixtures, compared to corresponding monocultures. Soil fauna diversity has, however, been previously observed to decline in field habitats with annual flower planting (similar to the 'sown flower' habitat type surveyed here) but increase with perennial plant species mixes [54]. As annual plants need to be replanted, while perennial plants do not, our observed decline in soil fauna diversity from TG to SF habitats may reflect greater disturbance due to re-sowing annual seeds and removing woody debris which acts as a habitat and food resource [24].…”
Section: Discussionsupporting
confidence: 65%
“…In their meta-analysis, Zhang et al [53] identified an average 10% increase in soil fauna diversity in more diverse plant mixtures, compared to corresponding monocultures. Soil fauna diversity has, however, been previously observed to decline in field habitats with annual flower planting (similar to the 'sown flower' habitat type surveyed here) but increase with perennial plant species mixes [54]. As annual plants need to be replanted, while perennial plants do not, our observed decline in soil fauna diversity from TG to SF habitats may reflect greater disturbance due to re-sowing annual seeds and removing woody debris which acts as a habitat and food resource [24].…”
Section: Discussionsupporting
confidence: 65%
“…Interesting results concerning annual and perennial flower strips located in areas adjacent to Poland (Germany) were obtained by Bednar et al [60]. They showed that strips of flowers with different life cycles are habitats for distinct communities of earthworms and soil microorganisms.…”
Section: Discussionmentioning
confidence: 99%